2002
DOI: 10.1002/cbm.492
|View full text |Cite
|
Sign up to set email alerts
|

Does self‐control account for the relationship between binge drinking and alcohol‐related behaviours?

Abstract: Further research is needed to disentangle the differences between the sexes. Situational factors, especially in males, may account for adverse alcohol-related behaviours. Other measures of self-control are also needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 31 publications
4
59
0
Order By: Relevance
“…However, the relationship between SR and alcohol use in college students is mixed. Although some studies failed to fi nd a relationship between SR and alcohol consumption (Carey et al, 2004;Neal and Carey, 2005), other studies have found that low SR or related constructs predicted a higher degree of alcohol involvement (Piquero et al, 2002;Werch and Gorman, 1988;Wills et al, 2002). Although undetected differences in samples may help explain these discrepant fi ndings, it is possible that the mixed fi ndings are related at least in part to method variance between studies; support against an SR and alcohol-use relationship employed the SSRQ to quantify generalized SR capacity, and support in favor of the relationship between SR and alcohol consumption relied on different self-report inventories.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between SR and alcohol use in college students is mixed. Although some studies failed to fi nd a relationship between SR and alcohol consumption (Carey et al, 2004;Neal and Carey, 2005), other studies have found that low SR or related constructs predicted a higher degree of alcohol involvement (Piquero et al, 2002;Werch and Gorman, 1988;Wills et al, 2002). Although undetected differences in samples may help explain these discrepant fi ndings, it is possible that the mixed fi ndings are related at least in part to method variance between studies; support against an SR and alcohol-use relationship employed the SSRQ to quantify generalized SR capacity, and support in favor of the relationship between SR and alcohol consumption relied on different self-report inventories.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, this research extended prior work of Piquero, Gibson, and Tibbetts (2002) that assessed Gottfredson and Hirschi's (1990) spuriousness hypothesis as it related to binge drinking and alcohol-related behaviors in two important ways. First, a stricter test of self-control theory was conducted by considering competing factors that were shown to be linked to the behaviors under investigation.…”
Section: Introductionmentioning
confidence: 88%
“…While many studies examined the effects of self-control on offending behaviors and deviant acts Burton, Evans, Cullen, Olivares, & Dunaway, 1999;Evans et al, 1997;Gibbs & Giever, 1995;Keane, Maxim, & Teevan, 1993;Piquero & Tibbetts, 1996;Polakowski, 1994), only one study, to the knowledge of the authors, used Gottfredson and Hirschi's (1990) theory to explain binge drinking and behaviors correlated with such practices (Piquero et al, 2002). Piquero and colleagues (2002) tested the spuriousness hypothesis of self-control theory as it related to drug use (binge drinking) and deviant behavior (alcohol-related behaviors).…”
Section: Introductionmentioning
confidence: 98%
“…These studies find support for self-control theory on topics including deviant behaviors including: Gambling, smoking, drinking, and drug use (Piquero, Gibson, & Tibbetts 2002;Arneklev et aI., 1993;Forde & Kennedy, 1997), bullying (Unnever, & Cornell 2003), victimization (Nofziger, 2009;Schreck, 1999Wilcox, Tillyer, & Fisher, 2009Tillyer, Fisher, & Wilcox, 2011), assault, burglary, and robbery (Grasmick, Tittle, Bursik, & Arneklev, 1993), and alcohol abuse (Piquero, Gibson, & Tibbetts, 2002).…”
Section: Theoretical Perspective: Self-control Theorymentioning
confidence: 92%
“…Researchers have linked low levels of self-control to a variety of deviant behaviors such as: Gambling, smoking, drinking, and illicit drug use (Piquero, Gibson, & Tibbetts 2002;Arneklev et aI., 1993; Forde & Kennedy, 1997), bullying (Unnever, & Cornell 2003), assault, burglary, and robbery (Grasmick, Tittle, Bursik, & Arneklev, 1993), victimization (Baron, Ford, & Kay, 2007;Piquero et aI., 2005;Schreck, 1999;Schreck, Stewart, & Fisher, 2006;Schreck, Wright, & Miller, 2002;Sullivan, Wilcox, & Ousey, 2011;Taylor, Peterson, Esbensen, & Freng, 2007;Wilcox, Tillyer, Fisher, 2009), and alcohol abuse (Piquero, Gibson, & Tibbetts, 2002). Pratt and Cullen (2000), found that self-control was consistently linked to causality as one of the strongest indicators of crime, as it was for any of the major criminological theories, thus solidifying its importance as a determinant of crime.…”
Section: Parental Managementmentioning
confidence: 99%